When we cease to understand the world - Labatut, Benjamín, 1980- (New York Review Books, 2021)
"A fictional examination of the lives of real-life scientists and thinkers whose discoveries resulted in moral consequences beyond their imagining. When We Cease to Understand the World is a book about the complicated links between scientific and mathematical discovery, madness, and destruction. Fritz Haber, Alexander Grothendieck, Werner Heisenberg, Erwin Schrodinger: these are some of luminaries into whose troubled lives Labatut's book thrusts the reader, showing us how they grappled with the most profound questions of existence. They have strokes of unparalleled genius, alienate friends and lovers, descend into isolation and insanity. Some of their discoveries reshape human life to the better; others pave the way to chaos and unimaginable suffering. The lines are never clear. At a breakneck pace and with a wealth of disturbing detail, Benjamin Labatut uses the imaginative resources of fiction to tell the stories of scientists and mathematicians who expanded our notions of the possible"--